Circular polarization of the high energy electron bremsstrahlung with account of the second Born approximation - Shul’ga, N.F.; Syshchenko, V.V. (Вопросы атомной науки и техники, 2007)
The estimation of contribution of the second Born approximation into circular polarization of bremsstrahlung from linearly polarized electrons is obtained. Account of this contribution could be important for correct interpretation of results of measurements of fine effects due to weak interactions. Отримано оцінку внеску другого борнiвського наближення до циркулярної поляризації гальмівного випромінювання лiнiйно-поляризованими електронами. Урахування цього внеску може бути важливим для коректної iнтерпретацiї результатів вимірювання тонких ефектів, що обумовлені слабкими взаємодіями. Получена оценка вклада второго борновского приближения в циркулярную поляризацию тормозного излучения линейно-поляризованными электронами. Учет этого вклада может быть важным для корректной интерпретации результатов измерения тонких эффектов, обусловленных слабыми взаимодействиями.